2019
DOI: 10.1194/jlr.d086884
|View full text |Cite
|
Sign up to set email alerts
|

A new method for measuring cholesterol efflux capacity uses stable isotope-labeled, not radioactive-labeled, cholesterol

Abstract: Supplementary key words apolipoprotein • reverse cholesterol transport • high density lipoprotein • mass spectrometry • stable isotope tracers • [d 7 ]cholesterol Many epidemiologic studies have reported an inverse relationship between coronary artery disease (CAD) events and HDL-cholesterol (HDL-C) levels (1-3). It is commonly known that the inhibition of cholesteryl ester transfer protein (CETP) leads to an increase in HDL-C levels in blood. Bowman et al. (4) recently reported that the inhibition of CETP by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Macrophage cholesterol efflux is the first critical step of RCT and considered as a key atheroprotective property [ 13 ]. The general methods for measuring cholesterol efflux capacity (CEC) include using radioisotope-labeled cholesterol that is labeled with [ 3 H]-cholesterol ([ 3 H]-C) and fluorescence-labeled cholesterol to measure CEC [ 14 , 15 ]. Impaired CEC has been proven to increase the risk of CVDs, which is independent of the plasma HDL-C levels [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Macrophage cholesterol efflux is the first critical step of RCT and considered as a key atheroprotective property [ 13 ]. The general methods for measuring cholesterol efflux capacity (CEC) include using radioisotope-labeled cholesterol that is labeled with [ 3 H]-cholesterol ([ 3 H]-C) and fluorescence-labeled cholesterol to measure CEC [ 14 , 15 ]. Impaired CEC has been proven to increase the risk of CVDs, which is independent of the plasma HDL-C levels [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Standard techniques employ cultured cells containing cholesterol labeled by radioisotopes to test HDL's efflux capacity, or ability to remove cholesterol from the serum [75], [76]. For example, J774, Raw264, or differentiated THP-1 cells are tagged with [3 H] cholesterol ([3H]C) and then treated with serum HDL, after which the radioactivity of [3H]C emitted by cells is assessed [77]. Due to the complexity of this treatment, it cannot be used in a clinical situation.…”
Section: Methods For Measuring Cholesterol Efflux Capacitymentioning
confidence: 99%
“…14 The incidence of cardiovascular disease is more inversely related to cholesterol efflux capacity, than to high density lipoprotein (HDL) levels. 15,16 Regarding foam cells, debate still remains as to the effect statins, specifically atorvastatin, have on initiating cholesterol efflux/reverse cholesterol transport (RCT). Some studies have reported an inhibitory effect of atorvastatin on foam cell models.…”
Section: Introductionmentioning
confidence: 99%